2020
DOI: 10.5267/j.msl.2020.2.029
|View full text |Cite
|
Sign up to set email alerts
|

Internet users’ attitudes towards social media advertisements: The role of advertisement design and users’ motives

Abstract: This research paper aims to examine the impact of social media advertisement attributes, including informativeness, trust, and irritation, and internet users' motivational factors; namely investigation, customization, opportunity seeking, interaction, and entertainment on individuals' attitude towards advertisements over social media sites in Jordan. A conceptual research model was proposed based on the relevant literature to be empirically tested. Data was collected using an online questionnaire survey admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…This finding is also supported by Shahbaznezhad et al's (2021) study, which indicated that content effectiveness on social media in terms of engaging audiences is highly affected by the context and different types of content. Another study by Haj Eid et al (2020) confirmed that consumers' attitude towards advertisements is influenced by the design of the ad, such as trust, information level, irritation, and interaction, as well as by users' attitudes.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…This finding is also supported by Shahbaznezhad et al's (2021) study, which indicated that content effectiveness on social media in terms of engaging audiences is highly affected by the context and different types of content. Another study by Haj Eid et al (2020) confirmed that consumers' attitude towards advertisements is influenced by the design of the ad, such as trust, information level, irritation, and interaction, as well as by users' attitudes.…”
Section: Introductionmentioning
confidence: 85%
“…The effects of advertising elements in social media, Facebook included, the intention to buy or click, and any other consumer actions that lead to a sale are a field that is studied well. The impact is found from the different ad elements, such as emotions evoking, especially positivity and humor (Taylor et al 2011;Wu et al 2018;Lee et al 2018), content informativeness level and type (Haj Eid et al 2020;Lutfie and Marcelino 2020), video ad length (Munsch 2021;Nettelhorst et al 2020;Raditya et al 2020), and content design (Al Kurdi and Alshurideh 2021;Xin Teo et al 2019). The importance in the same matters of information, entertaining content, advertising value, and being credible has also been confirmed by studies (Warsame et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Travel and tourism is a key industry in Jordan that contributes directly to the national income. This sector accounts for 19% of GDP, 8.8% of the total investment, and 5.1% of the total employment in 2016 (Koburtay et al, 2018;Eid et al, 2020). Further, the number of Jordanian traveling abroad for the purpose of tourism in 2018 and 2019 was 1,501,000 and 1,537,338, respectively, with an increase of 2.4%.…”
Section: Introductionmentioning
confidence: 99%
“…Users appreciate and like that SNS (Facebook) advertising which is relevant to their motivations for participating in SNS (Kaspar, Weber, & Wilbers, 2019). Several SNS studies (e.g., Eid, Nusairat, Alkailani, & Al-Ghadeer, 2020;Noguti & Waller, 2020) examined the relationship between several user motivations (e.g., building social capital, making social contact, getting emotional support, receiving excitement, past time, entertainment, information seeking ) and their approval of Facebook advertising.…”
Section: Introductionmentioning
confidence: 99%